2011
DOI: 10.1073/pnas.1109630108
|View full text |Cite
|
Sign up to set email alerts
|

Ancient host specificity within a single species of brood parasitic bird

Abstract: Parasites that exploit multiple hosts often experience diversifying selection for host-specific adaptations. This can result in multiple strains of host specialists coexisting within a single parasitic species. A long-standing conundrum is how such sympatric host races can be maintained within a single parasitic species in the face of interbreeding among conspecifics specializing on different hosts. Striking examples are seen in certain avian brood parasites such as cuckoos, many of which show host-specific di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 49 publications
(54 reference statements)
1
67
0
Order By: Relevance
“…Interestingly, four recent studies have identified mtDNA divergence where long periods of allopatry are less likely, all of which are in avian systems. This pattern has been observed between highland and lowland mtDNA clades of the rufous-collared sparrow (Zonotrichia capensis; Cheviron & Brumfield 2009), arid and mesic clades of the karoo scrub-robin (Cercotrichas coryphaeus; Ribeiro et al 2011), eastern and western clades of the greenish warbler (Phylloscopus trochiloides; Irwin et al 2005), and between tree-nesting and ground-nesting host parasites of the greater honeyguide (Indicator indicator; Spottiswoode et al 2011). While empirical examples of such phenomena are rare, simulation studies suggest that such phylogenetic breaks can arise in the absence of barriers to gene flow if dispersal and population sizes are low (Irwin 2002) or if selection favours different mtDNA haplotypes in different environments (Irwin 2012).…”
Section: Box 3 Mitochondrial Structure In the Absence Of Geographic mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, four recent studies have identified mtDNA divergence where long periods of allopatry are less likely, all of which are in avian systems. This pattern has been observed between highland and lowland mtDNA clades of the rufous-collared sparrow (Zonotrichia capensis; Cheviron & Brumfield 2009), arid and mesic clades of the karoo scrub-robin (Cercotrichas coryphaeus; Ribeiro et al 2011), eastern and western clades of the greenish warbler (Phylloscopus trochiloides; Irwin et al 2005), and between tree-nesting and ground-nesting host parasites of the greater honeyguide (Indicator indicator; Spottiswoode et al 2011). While empirical examples of such phenomena are rare, simulation studies suggest that such phylogenetic breaks can arise in the absence of barriers to gene flow if dispersal and population sizes are low (Irwin 2002) or if selection favours different mtDNA haplotypes in different environments (Irwin 2012).…”
Section: Box 3 Mitochondrial Structure In the Absence Of Geographic mentioning
confidence: 99%
“…Finally, a recent study of the greater honeyguide, an avian brood parasite in Africa, demonstrates strong mtDNA structure between individuals with ecologically distinct host species (ground-nesting birds versus tree nesters) with little to no structure in microsatellites (Spottiswoode et al 2011). By comparison, other taxa closely related to the greater honeyguide show much more nuclear divergence for the same mtDNA distance.…”
Section: Box 3 Mitochondrial Structure In the Absence Of Geographic mentioning
confidence: 99%
“…Honeyguides have two deeply diverged mitochondrial lineages, specialising on burrow-and hole-nesting hosts (Spottiswoode et al, 2011). The available data suggest that honeyguide host races have been host-specific (ground versus tree-nesting lineages) for a long time, but that gene flow through males has prevented host races from speciating.…”
Section: Mimicrymentioning
confidence: 99%
“…For example, brood parasitic Vidua finches, Vidua spp., underwent sympatric speciation as they annexed novel host species [15]. Moreover, specialization on particular host species has led to genetic divergence within some cuckoo and honeyguide species into distinct host-specific races [16][17][18], and Krü ger et al [19] demonstrated that species of parasitic cuckoos had more subspecies than species of non-parasitic cuckoos. Since the appearance of these studies, novel phylogenies [20] and phylogenetic methods [3,21] have been developed.…”
Section: Introductionmentioning
confidence: 99%